2020
DOI: 10.1029/2019jf005267
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistivity of Freezing Clay: Experimental Study and Theoretical Model

Abstract: Electrical resistivity of soil has become one of the most important indicators of compactness and compressive resistance. In previous studies, the temperature of soil tested was always above 0 °C. However, due to the phase change of pore water, the resistivity of freezing soils is different from that of unfrozen soils. Therefore, it is necessary to clarify the influence of temperature on electrical resistivity. To achieve this goal, according to the bundle of the cylindrical capillary model, pores in soil were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 89 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…These methods allow to characterize the spatial distribution of the electrical parameters (electrical conductivity, SP and so on) in a fast and non‐invasive manner. Recently, these electrical and electromagnetic methods have gained a strong interest in the field of permafrost, frozen porous media as well as snowmelt infiltration, for example, to characterize the thaw layer thickness dynamics (e.g., Dafflon et al., 2013; Duvillard et al., 2018; Murton et al., 2016; Pedrazas et al., 2020) or to measure the liquid water content in frozen porous media (Coperey, Revil, Abdulsamad, et al., 2019; Ming et al., 2020; Oldenborger & LeBlanc, 2018). For instance, the zeta potential is very sensitive to the temporal evolution of snow porosity, pH and meltwater flux, which is important in snowmelt and liquid water‐ice phase change systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods allow to characterize the spatial distribution of the electrical parameters (electrical conductivity, SP and so on) in a fast and non‐invasive manner. Recently, these electrical and electromagnetic methods have gained a strong interest in the field of permafrost, frozen porous media as well as snowmelt infiltration, for example, to characterize the thaw layer thickness dynamics (e.g., Dafflon et al., 2013; Duvillard et al., 2018; Murton et al., 2016; Pedrazas et al., 2020) or to measure the liquid water content in frozen porous media (Coperey, Revil, Abdulsamad, et al., 2019; Ming et al., 2020; Oldenborger & LeBlanc, 2018). For instance, the zeta potential is very sensitive to the temporal evolution of snow porosity, pH and meltwater flux, which is important in snowmelt and liquid water‐ice phase change systems.…”
Section: Introductionmentioning
confidence: 99%
“…In response to this shortcoming, the third type includes the capillary bundle models of electrical conductivity of frozen porous media, which consider either a variable PSD or the physical properties of the solid surface-liquid water interface. Recently, Ming et al (2020) calculated the liquid water content in frozen soils by establishing the cylindrical capillary electrical conductivity model from a mathematical point of view. Even if the impact of PSD on electrical conductivity is considered, this model does not consider the influence of surface conductivity at the solid surface-liquid water and bulk ice-liquid water interfaces in frozen porous media, and the physical relationship between electrical conductivity and basic soil properties such as porosity, liquid water content, permeability or cation exchange capacity remains unclear.…”
mentioning
confidence: 99%
“…Moreover, pore sizes are small in fine‐grained sediments and the growth of miniscule ice crystals developing in such confined spaces during freezing is hindered by thermodynamic surface effects (Dash, 1989). Consequently, laboratory freezing experiments on fine‐grained sediments show that small amounts of liquid water persist down to at least −20°C and that the electrical resistivity of such sediments remains relatively low (Ming et al., 2020). For these reasons, we interpret that increasing soil conductivities in all three transects are due to increases in solute contents and fine‐grained sediment fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Figure 8b shows that the depth to the top of a talik can be shallower if the freezing point depression is 2 °C. Recent studies based on laboratory measurements of the resistivity response during freezing of porous media showed that above 0 °C, the bulk resistivity is controlled by the pore water resistivity which increases with decreasing temperature, and below 0 °C, the bulk resistivity depends on the unfrozen water content and its resistivity (Herring et al., 2019; Ming et al., 2020). This evidence suggests that TEM measurements can detect partially unfrozen saline pore water in remnant taliks, since electrical current can flow through very small pore spaces.…”
Section: Discussionmentioning
confidence: 99%